Estudio y análisis de factibilidad para la implementación de una red de fibra óptica que brinde servicios de telefonía fija e internet banda ancha a la parroquia Poaló por parte de la Empresa E&E Ingenieros. - Corrales Caiza, Kevin Guillermo (2021)
The project: "STUDY AND FEASIBILITY ANALYSIS FOR THE IMPLEMENTATION OF AN OPTICAL FIBER NETWORK THAT PROVIDES FIXED TELEPHONE AND BROADBAND INTERNET SERVICES TO POALÓ PARISH BY THE COMPANY E&E INGENIEROS," aimed to improve an essential aspect of the daily use of the human being, as it is in these current times, using communication tools. The use of communication networks such as the internet, bring benefits and conveniences for the human being. One of the most named benefits of this tool is its speed when transmitting data. All this will be studied in the research, among other factors that will benefit this rural sector. The analysis will be generated through a research proposal to developing in computer software. The project will allow the inhabitants to obtain all the benefits generated by installing fiber optics, allowing them to visualize the design and obtain the financial budget that will indicate all the necessary investment to implement this fiber optics in the rural sector of Poaló.